THE ROLE OF THE 18TH ASIAN GAME IN THE PEACE OF THE KOREAN PENINSULA - Abdul Rodhi , Nadia; Paksi , Arie Kusuma (Jurnal Ilmiah Dinamika Sosial, 2021)
This journal examines the role of the 18th Asia Game as a diplomatic tool in the Korean peninsula conflict in 2018, specifically in promoting peace on the Korean Peninsula. This journal aims to describe and analyze the effectiveness of sports or Olympics affiliated with the Olympic Council of Asia (OCA) as a unifying tool in pushing for reunification opportunities on the Korean Peninsula. The 18th Asian Games, on the other hand, has played an essential role in uniting North and South Korea into one unit under the same flag in a variety of ways that have had a positive impact on peace between the two countries. This study employs qualitative research methods, such as literature review and triangulation, to collect data. A descriptive-analytical approach was used to collect and analyze data. This study's analysis employs sports diplomacy theory to examine the effectiveness of sports in resolving conflicts on the Korean Peninsula. Because the current state of the Korean peninsula has not entirely resulted in the ideals of the two countries' reunification, the theory of sports diplomacy can identify the factors that support the reduced intensity of the Korean Peninsula's cold war. One of the factors is the role of sport as a tool of sports diplomacy, which has increased opportunities for promoting peace and conflict resolution to reach a peace agreement between the two parties and eventually lead to reunification.